Is the Proportion of College Workers in Noncollege Jobs Increasing? - Gottschalk, Peter; Hansen, Michael (Journal of Labor Economics, 2003)
This article explores the claim that college‐educated workers are increasingly likely to be in “noncollege” occupations. We provide a conceptual framework that gives analytical content to the previously vague distinction between “college” and noncollege jobs. We show that, when there is heterogeneity in preferences, equally productive college workers can be in college and noncollege jobs. This framework is also used to show that skill‐biased technological change will lead to a decline in the proportion of college workers in noncollege jobs. This prediction is supported by the data.